2018
DOI: 10.3389/fmicb.2018.02142
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Ammonium Oxidation in Acidic Red Soils

Abstract: Anaerobic ammonium oxidation (anammox) has been proven to be an important nitrogen removal process in terrestrial ecosystems, particularly paddy soils. However, the contribution of anammox in acidic red soils to nitrogen loss has not been well-documented to date. Here, we investigated the activity, abundance, and distribution of anammox bacteria in red soils collected from nine provinces of Southern China. High-throughput sequencing analysis showed that Candidatus Brocadia dominates the anammox bacterial commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 60 publications
1
6
1
Order By: Relevance
“…We investigated N 2 production rates and processes across ∼2,500 km continental shelf sediment transect along coastline in eastern China (Figure 1) and found that denitrification process dominated N 2 production with the average relative contribution of 90% and ranged from 0.03 to 9.73 nmol N 2 g −1 h −1 (Figure 1 and Figure S3 in Supporting Information S1). Our measured N 2 production rates by denitrification were comparable to previous studies in marine and estuarine sediments (Gao et al., 2016; Lin et al., 2017) and in terrestrial ecosystems (Gu et al., 2017; Tang et al., 2018; Wu et al., 2018; Xi et al., 2016). Additionally, sediment denitrification rates in the studied regions are higher than the rates from sea water columns in some coastal regions (Dalsgaard et al., 2013; Seitzinger, 1988), confirming the estimate from models that sedimentary denitrification rate may be higher than suboxic zones (DeVries et al., 2013).…”
Section: Discussionsupporting
confidence: 90%
“…We investigated N 2 production rates and processes across ∼2,500 km continental shelf sediment transect along coastline in eastern China (Figure 1) and found that denitrification process dominated N 2 production with the average relative contribution of 90% and ranged from 0.03 to 9.73 nmol N 2 g −1 h −1 (Figure 1 and Figure S3 in Supporting Information S1). Our measured N 2 production rates by denitrification were comparable to previous studies in marine and estuarine sediments (Gao et al., 2016; Lin et al., 2017) and in terrestrial ecosystems (Gu et al., 2017; Tang et al., 2018; Wu et al., 2018; Xi et al., 2016). Additionally, sediment denitrification rates in the studied regions are higher than the rates from sea water columns in some coastal regions (Dalsgaard et al., 2013; Seitzinger, 1988), confirming the estimate from models that sedimentary denitrification rate may be higher than suboxic zones (DeVries et al., 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Anammox diversity in the terrestrial systems was higher in soil than in freshwater environments; for example, in wetland and dryland soils, three different genera of anammox bacteria were detected, including “ Candidatus Kuenenia,” “ Candidatus Brocadia,” and “ Candidatus Jettenia” ( Zhao et al, 2018 ). In acidic red soils, anammox bacteria were related to “ Candidatus Brocadia,” “ Candidatus Scalindua,” “ Candidatus Kuenenia,” and “ Candidatus Anammoxoglobus” ( Wu et al, 2018 ). The above discussions indicated that in natural ecosystems, the highest diversity of anammox bacteria occurred in terrestrial systems, followed by freshwater systems and marine systems, which was in accordance with our finding that anammox bacteria had a higher diversity in hot springs.…”
Section: Discussionmentioning
confidence: 99%
“…High‐throughput sequencing was performed using Mothur software V1.40.5 according to the standard protocol, as described previously by Schloss et al (2009) and Wu et al. (2018). In short, the tags and primers were removed from quality‐controlled sequences.…”
Section: Methodsmentioning
confidence: 99%
“…The pre.cluster , chimera.uchime and remove.seqs commands were used to reduce errors and remove chimeras. To conduct further diversity analyses, representative sequences were gathered into operational taxonomic units (OTUs) as defined by 97% sequence identity through the dist.seqs , cluster , make.shared , and classify.otu commands (Wu et al., 2018; Zhao et al., 2013). Rarefaction curves and Principal Coordinates analyses (PCoA) were conducted by the rarefaction.single and pcoa commands, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation